Pengaruh Karakteristik CEO terhadap Kinerja Perusahaan pada Perusahaan Sektor Transportasi dan Logistik di Indonesia - Wijaya, Ferencia Maria; Safitri, Rika Henda; Yuniartie, Emylia (Politeknik Ganesha Medan, 2024)
This research aims to examine the influence of CEO characteristics on company performance. The study employs a quantitative paradigm by processing secondary data resource. The population consists of transportation and logistics sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample size for this study is 70 companies, selected using purposive sampling and analyst by multiple linear regression analysis. Calculating performance based on Tobin’s Q, the results indicate that CEO Narcissism and CEO Education do not significantly affect Company Performance. CEO Gender has a positive impact on Company Performance, while CEO Tenure has a negative influence on Company Performance.